2016
DOI: 10.1088/2043-6262/7/4/045015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rutile titania dioxide nanoparticles on the mechanical property, thermal stability, weathering resistance and antibacterial property of styrene acrylic polyurethane coating

Abstract: This study aims to enhance the mechanical properties, thermal stability, weathering resistance and antibacterial property of a styrene acrylic polyurethane coating by adding rutile titania dioxide (R-TiO2) nanoparticles in coating formulation. The styrene acrylic polyurethane/R-TiO2 nanocomposite had been prepared by using ultrasonication. The effects of nanoparticles on the mechanical properties, thermal stability and weathering resistance of as-prepared coatings were investigated by using the adhesion streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 35 publications
5
29
0
Order By: Relevance
“…Adding these additives at appropriate content could increase the weathering durability of the polymer coatings by 2-3 times [3]. Besides, as reported in literature, some metal oxides (TiO 2 , ZnO, ZrO 2 ) can absorb ultraviolet (UV) rays, therefore having an ability to protect the polymer substrates from harmful UV light [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Adding these additives at appropriate content could increase the weathering durability of the polymer coatings by 2-3 times [3]. Besides, as reported in literature, some metal oxides (TiO 2 , ZnO, ZrO 2 ) can absorb ultraviolet (UV) rays, therefore having an ability to protect the polymer substrates from harmful UV light [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 96%
“…In order to improve the weathering resistance of the outdoor coatings, in addition to selecting the main components such as resins and pigments with high weathering durability, organic and inorganic light stabilizing additives are usually added to the paint formulation [3][4][5][6][7]. Previous published works showed that organic light stabilizers (such as Tinuvin 384, Tinuvin 1130, Tinuvin 292) exhibited an excellent light stabilizing efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…3. This is due to the formation of covalent bonds between the solvent and hardener molecules into Curcuma Longa pigment of the thin film coating and substrate of metal surfaces to enhance the adhesion resistance [6]. Figure 3 The results of classification of adhesion test (B) at different percentages of Curcuma Longa of 20%, 40%, 60% and 80% for 3, 6 and 9 layers.…”
Section: Adhesion Testmentioning
confidence: 99%
“…reported that the dispersion of TiO 2 NPs dominated the acrylic PU surface morphological changes during UV radiation and greatly affected the filled coatings degradation process. In another study, however, Nguyen et al . indicated that the rutile TiO 2 NPs mitigated the chemical change, weight loss, and mechanical degradation of the styrene acrylic PU coating, but exhibited a photocatalytic effect in the inhibition of E. coli bacterial growth.…”
Section: Introductionmentioning
confidence: 96%
“…Nowadays, TiO 2 NPs is showing a new approach for notable applications as an attractive multifunctional material, especially in photocatalysis, catalysis self‐cleaning, UV‐protecting agents, and environmental purification . TiO 2 NPs exhibited a broad spectrum of activity against microorganisms, including positive‐bacteria, Gram‐negative, and fungi and also inhibit the growth of pathogens including bacteria, viruses, and cancer cells under mild UV‐light irradiation . Its antibacterial activity is attributed to the hydroxyl radicals and reactive oxygen species (ROS) generated on the surface of illuminated TiO 2 and inactivate the microorganism by oxidizing the polyunsaturated phospholipid components of the microbes' cell membrane …”
Section: Introductionmentioning
confidence: 99%